2021
DOI: 10.1002/agj2.20817
|View full text |Cite
|
Sign up to set email alerts
|

Corn response to row spacing and plant population in the Mid‐South United States

Abstract: Core ideas (3-5 impact statements, 85 char max for each)  Narrow rows (48 cm vs. 96 cm) increased grain yield by 5% (0.69 Mg ha -1 )  Narrow rows increased stalk diameter and produced two more kernels per row  Agronomic optimum plant populations ranged from 104-119 thousand ha -1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Density (Van Roekel and Coulter, 2011) or population of maize plants (Williams et al, 2021) Relationship between weed density and yield loss (Cousens, 1985)…”
Section: Regression Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Density (Van Roekel and Coulter, 2011) or population of maize plants (Williams et al, 2021) Relationship between weed density and yield loss (Cousens, 1985)…”
Section: Regression Modelsmentioning
confidence: 99%
“…Experiments that study quantitative factors in agricultural sciences have been reported in several articles such as studies of plant density or population (Van Roekel and Coulter, 2011;Williams et al, 2021), fruit post-harvest quality (Marodin et al, 2016), seed germination (Motsa et al, 2015), weed control (Noel et al, 2018), and growth curves (Lúcio and Sari, 2017). In these studies, polynomial models were predominantly used and, although this is not incorrect, many natural phenomena do not present such behavior but rather specific models (Archontoulis and Miguez, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Lobell et al (2009) and Beza et al (2017) outlined several biophysical factors including nutrient deficiencies, water stress, flooding, planting issues, soil problems, weed pressures, insects, diseases, and lodging, as well as socioeconomic factors such as risk aversion, inexperience, and economic issues. Numerous agronomic strategies exist to improve corn production in Mississippi: substituting crop yield goals (Oglesby et al, 2022) for remote sensing based N management (Dhillon et al, 2020;Sumner et al, 2021), irrigation scheduling using soil moisture sensors (Spencer et al, 2019), crop rotation (Abbas et al, 2012), adopting site-specific optimum plant densities (Williams et al, 2021), proper hybrid selection (Walne & Reddy, 2021;Williams et al, 2020), and optimum planting dates (Williams et al, 2018).…”
Section: Reasons For Yield Gapmentioning
confidence: 99%
“…Since the 1960s, the average corn plant population has been increasing at a rate of 400 plants acre −1 year −1 , reaching current average of 32,000 plants acre −1 (Bernhard & Below, 2020), with corresponding increase in grain yield (Assefa et al., 2016). Specifically, agronomic optimum plant population of 41,600 and 47,600 plants acre −1 was noted for Mississippi, depending upon site‐year (Williams et al., 2021). Intraspecific competition for nutrients, moisture, and sunlight increases as plant density increases (Assefa et al., 2018).…”
Section: Introductionmentioning
confidence: 99%